(untitled) (Iter, 2022)
In his treatise O n the sp e c ia l laws 3, Philo of Alexandria organizes and explains the biblical laws about marriage and sexuality and includes among them one which prohibits Jews to marry “a person from another nation” (aXXo£0v£i) (Spec. 3.29). Since this absolute interdiction lacks a specific source in the Pentateuch, our study aims to inquire the reasons why Philo assumes such an adverse posture towards mixed marriages. With this goal, we will analyze, in the first place, the passages from the Torah which could have functioned as an exegetical basis -Dt 7.3-4, Ex 34.16, Dt 23.4- even though none of them reaches the universality that Philo assigns to the prohibition. In the second place, we will examine other passages of Philos work in which he manifests his attitude towards mixed marriages; in particular, his interpretation of biblical stories about unions between Hebrews and foreign slaves, such as those of Abraham with Hagar (O n A b r a h am 250-254) and of Jacob with Leah and Rachel (O n v ir tu e s 223-225), among others. By means of this analysis, we will try to demonstrate the hypothesis that Philos position towards mixed marriages is connected with the unstable socio-political condition of the Jewish community’ in the city of Alexandria under the rule of the Roman Empire, at the same time that it receives a strong influence from Greek and Roman legal statutes for the transmission of citizenship.